The Existence Of Truck Driver In The Spirit Of Work - Mochamad Mochklas; Noerchoidah; Nurullaili Mauliddah; Tyasha A. M. Sari (Fakultas Ekonomi dan Bisnis, Universitas Tarumanagara, 2023)
The role of truck drivers in sustainable transportation and logistics in a sustainable supply chain network is particularly noteworthy. The driver work system is very different from the employees in the company. Therefore, this research was conducted to analyze the effect of work passion, strength against frustration, quality of survival, and team spirit on the morale of truck drivers in their delivery activities. This study used a quantitative approach with 173 truck drivers participating as respondents. Testing using SEM analysis with the SmartPLS 3.0 application. The results showed that work passion, strength against frustration, quality of endurance, and group spirit each had a unidirectional relationship with morale, meaning that the higher the passion for work, the strength against frustration, the quality of survival, and the group spirit of truck drivers, the higher the morale will increase. Based on the coefficient value, it can be seen that the quality of survival is a predictor that has a dominant influence on morale, which is indicated by the highest coefficient of 0.288.